(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
Based on data from the Kebumen District Health Service, the results of the performance of the TB program in the Kebumen District area which includes 35 Community Health Centers and several hospitals in 2020-2022 achieved a significant increase where in 2020 the CDR was reported as 71% and in 2021 79% from the target of 90% Meanwhile, in 2022 CDR is reported to have only reached 21% of the target of 95%.One effort to empower the community in the tuberculosis control program is to involve managers through educational activities and support from health cadres. Objective to determine the performance of TB cadres in achieving TB suspects at Kebumen II Community Health Center. Method: This research is quantitative descriptive research. The sample taken by TB cadres was 22 people using total sampling technique. Data analysis used univariate analysis. Results: The performance of TB cadres as seen based on educational background, the majority are at primary and secondary education levels (45.5%), the majority’s attitude is good (81.8%), knowledge (100%) is good. the majority’s motivation is good (72.7%), (100%) they have received training, their abilities/skills (100%) are good, the majority have worked > 1 year (90.9%), the facilities and infrastructure are in the majority category support (90.9%). The performance of TB cadres in achieving the majority of TB suspects at Kebumen II Health Center is good. The better the performance, the maximum the target of achieving TB case detection. Keywords: Performance, Health Cadres, TBC